MicroRNA-15b-5p inhibits tumor necrosis factor alpha-induced proliferation, migration, and extracellular matrix production of airway smooth muscle cells via targeting yes-associated protein 1. Issue 3 (1st March 2022) - Zeng, Shaolin; Cui, Juan; Zhang, Yunting; Zheng, Zhishui; Meng, Jun; Du, Junying
ABSTRACT: The excessive proliferation and the deposition of extracellular matrix (ECM) of airway smooth muscle (ASM) cells facilitates airway remodeling in asthma. This study explores how microRNA-15b-5p (miR-15b-5p) functions in modulating the proliferation, migration, inflammatory response, and ECM deposition of ASM cells. MiR-15b-5p and yes-associated protein 1 (YAP1) mRNA expression levels in tumor necrosis factor alpha (TNF-α)-induced ASM cells were, respectively, examined by real-time quantitative polymerase-chain reaction. Besides, the proliferative ability and migrative potential of ASM cells were examined by cell counting kit-8 assay, 5-bromo-2 '-deoxyuridine assay, and transwell assays, respectively. Interleukin-6 and interleukin-8 levels in ASM cells were detected by enzyme-linked immunosorbent assay. YAP1, collagen I, and collagen III expressions in ASM cells were detected by Western blot. With dual-luciferase reporter gene assay, the relations between miR-15b-5p and YAP1 3ʹUTR in ASM cells was examined. MiR-15b-5p expression level was reduced in ASM cells treated with TNF-α. MiR-15b-5p repressed TNF-α-initiated growth and migration of ASM cells and also suppressed IL-6 and IL-8 secretion, and inhibited collagen I and collagen III expressions in ASM cells. Furthermore, it was validated that YAP1 was a downstream target of miR-15b-5p in ASM cells. Notably, YAP1 overexpression attenuated the inhibitory effects of miR-15b-5p up-regulation on the proliferation, migration, and inflammatory response, as well as ECM deposition of TNF-α-induced ASM cells. In conclusion, miR-15b-5p/YAP1 axis modulates the growth, migration, inflammatory response, and ECM deposition of ASM cells, thus participating in the pathogenesis of asthma. Graphical Abstract: uf0001